EFFECT OF NABUMETONE ON CELLULAR IMMUNE RESPONSES IN MICE - K. Naveed; A. Javeed1; M. Ashraf; A. Riaz; S. Khurram; A. Sattar; A. Ghafoor (Journal of Animal and Plant Sciences, 2020)
Nabumetone is used to control pain and inflammation in rheumatoid arthritis. It works through inhibition of cyclo-oxygenases (COX), especially COX-2. In the current study, Nabumetone immunomodulatory effect was detected on cellular immunity in mice. The control group was administered normal saline orally as placebo. Nabumetone was administered orally in two treatment groups 14mg/kg and 28mg/kg, respectively by gavage needle. Macrophage engulfment, delayed type hypersensitivity (DTH), nitric oxide measurement and cyclophosphamide induced neutropenia assays were used to evaluate the immunomodulatory effects. In DTH, there was more thickness of the skin in control than Nabumetone treatment groups (p≤0.05). In the macrophage engulfment assay, a significant decrease (p≤0.05) in engulfment percentage was observed in treatment groups. In cyclophosphamide induced neutropenia, the levels of TLC and DLC were higher in the control group (p≤0.05). In the nitric oxide measurement assay, there was a significant reduction in nitric oxide production at higher doses of Nabumetone (p≤0.05). Therefore, it is concluded that Nabumetone suppress cellular immune responses in mice.
Keywords: Nabumetone; Cellular immunity; Nitric oxide; Macrophages